Comparative testing of MOST and Mac-Cormack numerical schemes to calculate tsunami wave propagation. (November 2020) - Lavrentiev, M; Marchuk, An; Oblaukhov, K; Romanenko, A
Abstract: The problem of fast, reliable, and accurate calculation of tsunami wave propagation is addressed. Based on the shallow water approximation, two numerical approaches to calculate tsunami wave propagation are compared at the same computational mesh. To evaluate precision of numerical solutions the available exact solutions (for the cases of sloping and parabolic bottom) are used. Results of several numerical tests are presented. Time required to obtain tsunami wave height maxima distribution is briefly discussed, too.